Function of TRP channels in monocytes/macrophages - Wu, Jiangbo; Li, Zhuo; Deng, Ya; Lu, Xianmin; Luo, Chen; Mu, Xingyi; Zhang, Ting; Liu, Qi; Tang, Siqi; Li, Jiajing; An, Qimin; Fan, Dongdong; et al. (Frontiers in Immunology, 2023)
The transient receptor potential channel (TRP channel) family is a kind of non-specific cation channel widely distributed in various tissues and organs of the human body, including the respiratory system, cardiovascular system, immune system, etc. It has been reported that various TRP channels are expressed in mammalian macrophages. TRP channels may be involved in various signaling pathways in the development of various systemic diseases through changes in intracellular concentrations of cations such as calcium and magnesium. These TRP channels may also intermingle with macrophage activation signals to jointly regulate the occurrence and development of diseases. Here, we summarize recent findings on the expression and function of TRP channels in macrophages and discuss their role as modulators of macrophage activation and function. As research on TRP channels in health and disease progresses, it is anticipated that positive or negative modulators of TRP channels for treating specific diseases may be promising therapeutic options for the prevention and/or treatment of disease.